Selective Importance in Self-Enhancement: Patterns of Feedback Adolescents Use to Improve Math Self-Concept. (February 2021) - McPartlan, Peter; Umarji, Osman; Eccles, Jacquelynne S.
We illustrate how early adolescents use different patterns of ability feedback to promote a positive self-concept of ability (SCA) in mathematics. Students can simultaneously use ability appraisals from parents and teachers, while also drawing information from peer, dimensional, and temporal comparisons. Although we find these five sources are equally important for promoting students' positive SCA, on average, we use a pattern-centered approach to show that students who believe they are good at math often select certain feedback sources as more important to develop this belief. We find that students' patterns of ability feedback are unstable, with evidence suggesting different patterns may emerge depending on the availability of ability feedback. Findings suggest early adolescents attempting to promote their own positive SCA in mathematics may know to seek different feedback sources depending on their individual circumstances. Implications are discussed through the lens of social comparison theory.